Alcoholism in familiar and social context: documental analysis by Pimentel light - Jorge, Maria Salete Bessa; Lopes, Consuelo Helena Aires de Freitas; Sampaio, Cynthia de Freitas; Souza, Lyara Veríssimo de; Silva, Michelle Soares Joseno da; Alves, Marcela Soares (Rev Rene, 2007)
The alcohol is one of the few psychoactive drugs which consume is socially accepted and even incentived by the society.The objective was to analyze the scientific production about alcoholism in Nursing magazines in the period of 2000 to 2005 and its repercussion in the social and familiar context, to confront ideas of the authors found in the literature about the theme, to show the interventions of the health team on the alcoholic patient, regarding to Brazilian articles. It is a bibliographic study, with referenced analysis by Pimentel (2001). The results indicated the thematic nucleus: explicative models about the phenomenon of the use of alcohol, alcohol versus multifatoriality, risk groups, family relations and life quality of the alcoholic patients, interventions of the health team. Although the studies make clear the malefic consequences of the alcohol abuse, it is still considered as insufficient to manage the diverse dimensions of the studied phenomenon, having need of other investigations that subside the professional interventions.